Pengaruh Independensi, Gaya Kepemimpinan, Komitmen Organisasi, Pemahaman Good Governace, Dan Etika Profesi Terhadap Kinerja Auditor (Studi Kasus Pada Kantor Akuntan Publik Di Wilayah Jawa Tegah) - Nalendra, Fradilla Septia, Drs. Suyatmin Waskito Adi, M.Si (2016)
The purpose of this study was to analyze the effect of Independence, Leadership Style, Organizational Commitment, Understanding Good Governance and Performance Against Auditor Professional Ethics (Case Study in Public Accountant Regional Central Java). The population used in this study were all auditors working in the public accounting firm in the region of Central Java. The data used in this study are primary data by distributing questionnaires. Sampling was determined using purposive sampling method, with the predetermined criteria. The sample in this study were 45 respondent. This study tested using multiple regression models (multiple regression). The results of this study indicate that the Independence, Leadership Style, Organizational Commitment, Understanding Good Governance and Professional Ethics affect the auditor's performance and can improve the quality of work of auditors.